Twardowski on Truth - SIMONS, PETER (The Baltic International Yearbook of Cognition, Logic and Communication, 2009)
Of those students of Franz Brentano who went on to become professional philosophers, Kazimierz Twardowski (1866-1938) is much less well-known than his older contemporaries Edmund Husserl and Alexius Meinong. Yet in terms of the importance of his contribution to the history of philosophy, he ranks among Brentano?s students behind at most those two, possibly only behind Husserl. Notice that I did not say ?the history of philosophy in Poland? but ?the history of philosophy?. This may seem surprising for a philosopher whose writings and even name are very little known outside his native country. The only work of Twardowski likely to be known at all is his 1894 Vienna Habilitationsschrift Zur Lehre vom Inhalt und Gegenstand der Vorstellungen [On the Content and Object of Presentations], which strongly and decisively influenced both Meinong and Husserl in their accounts of the structure of intentionality. That work was translated into English by Reinhardt Grossmann and published in 1977. I share Reinhardt?s estimation* (echoing that of Findlay*) that it is one of the most accomplished short monographs in all philosophy and deserves to be considered a classic. It disambiguates Brentano?s 1874 work on intentionality, distinguishing the content of an idea from its object, supporting the distinction with examples and arguments, and cementing it terminologically. It does for content and object what Frege had done for sense and reference just two years earlier. It is written with limpid clarity, an abiding feature of Twardowski?s work. Important as it is for the immediate history however, it is not the main reason why Twardowski is so important. That importance rests in no small part on Twardowski?s teaching and organizational activity, carried out after he took up his Extraordinariat in Lwow in 1895 at the age of 29 and until his retirement in the 1930s. Twardowski found philosophy in Poland in a parlous state. Up until 1918 philosophy in Poland was essentially confined to two centres, Krakow and Lwow in Austrian-administered Galicia, where instruction in Polish was allowed. In Warsaw, where some higher education was permitted in Russian, though the University had been closed then reopened as a non-university then Russified following the abortive uprisings of 1830 and 1863 Henryk Struve, the only philosopher of note, emigrated to Britain in 1903 and that, until the Gemans reopened the University in 1915, was that. According to Wladyslaw Tatarkiewicz?s Zarys dziejow filozofii w Polsce (A Brief History of Philosophy in Poland), published in 1948* (Tartarkiewicz was yet another former Twardowski student), Polish philosophy in the 19th century had been an eclectic mixture of Scottish common sense philosophy, Kantianism, a romantic nationalistic Messianism and after 1863 what was known as Warsaw Positivism. None of it was of international standard. Twardowski saw that to promote good academic (Brentanian) philosophy in Poland he would have to sacrifice his career as a writer for one as a teacher and organiser, and his unparalleled influence on the philosophical life of a nation bears testimony to his success. Within twenty years he had gathered a cohort of the best students round him in Lwow, who would after the war go on to people thirty chairs, including ten of philosophy, around the Second Republic, make Poland one of the chief centres of scientific-analytic philosophy in the world, and the world centre of mathematical logic. All this is well documented.
PUBLISHED
Keywords: Philosophy